ALAT BANTU LIFTER PLATE KAPASITAS 100 KG - Dwiky Tito Cahya Aprilian; Bayu Wiro Karuniawan; Thina Ardliana (Proceedings Conference On Design Manufacture Engineering And Its Application, 2022)
In today's industrial world, especially in large companies or factories, of course, they need tools to move goods. At PT Nas Teknologi Indonesia, the product that uses a plasma cutting machine is plate material. The process of lifting the plate to the work table of the plasma cutting machine requires a minimum workforce of 2 to 5 people and each worker has their own jobdesk so that during the plate lifting process the workers stop their work for a while to help the plate lifting process. Therefore, to help workers at PT Nas Teknologi Indonesia, tools are needed to lift plate materials such as Hand Pallets, Forklifts and Hand Stackers. The process of making this tool uses the Ulrich method, starting from the needs of the tool to the selection of concepts and design embodiments. Then planning, calculation and analysis will be carried out to determine the components to build the tool. The next stage is to make detailed drawings of the plate lifting equipment and proceed with the fabrication process. In testing the lifting plate is able to lift a plate weighing 100 kg with a height of 50 cm and a distance of 30 meters. This tool produces a time of 1 minute 32 seconds with a total required budget of Rp. 5,929,000.